Economic performance of motorised and non-mechanised fishing methods during and after-ban period in Ramanathapuram District of Tamil Nadu - Johnson, B.; Narayanakumar, R.; Swathilekshmi, P. S.; Geetha, R.; Ramachandran, C. (Indian Journal of Fisheries, 2018)
Ramanathapuram is an important coastal district significantly contributing to the marine fish production of Tamil Nadu State. The coastal length, number of fishing villages and fishing activities is more in Ramanathapuram District in comparison to other coastal districts in Tamil Nadu. The present study analysed the economic performance of motorised and non-mechanised craft-gear combinations during and after-ban period in Ramanathapuram District. In motorised single day craft-gear combinations, the capital productivity was higher during ban, period in comparison with after-ban period, with a lower operating ratio ranging from 0.55 for gillnetter to 0.58 for bottom-set gillnetter. In motorised multi-day craft-gear combinations, the capital productivity during ban,was more in comparison with after-ban period with a lower operating ratio of 0.64 for trawler and gillnetter. In non-mechanised craft-gear combinations, during ban, the capital productivity was higher in comparison with after-ban period with a lower operating ratio ranging from 0.49 for gillnetter to 0.52 for bottom-set gillnetter. It was found that during ban period, capital productivity was high in non-mechanised gillnetter and bottom set gillnetter, while the catch, labour productivity and income were high in multi-day (2-4 days) trawler and gillnetter.